Correlation between Quality of Sleep and Libido of Male Factory Workers at PT Sritex, Sukoharjo - Rico Alfredo; Andri Iryawan; Rosalia Sri Hidayati (Nexus Kedokteran Komunitas, 2017)
Introduction: Indonesia has the highest divorce rate in Asia-Pacific by reason of household disharmony in which one of the sources of problems that can be a cause of its bad sexual relationship . Good quality sleep affects the body's testosterone levels and affect the sexual libido which is needed as a contributing factor in the sexual relationship . This study aims to determine the correlation between quality of sleep and libido of male factory workers at PT Sritex , Sukoharjo.Methods: This research was an analytical study with cross sectional approach, conducted in PT Sritex, Sukoharjo in November 2015. The sample size was 45 male factory workers that worked at night shift. They were chosen by purposive random sampling and in accordance with the inclusion and exclusion criteria that have been established. Data obtained from the questionnaires Pittsburgh Sleep Quality Index to assess the quality of sleep and hypoactive Sexual Desire Disorder (HSDD) Screener to assess libido. The data were tested using chi-square analysis using the Statistical Product and Serve Solution (SPSS) for Windows.Result: Chi-square analysis test showed the value of Asymp. Sign obtained 0,02. Contingency coefficient value is 0.423 (p = 0.02, C = 0.423).Conclusions: The result showed that there was significant relationship between sleep quality with libido, but the relationship between the variables were relatively weak. Keywords: sleep quality, libido, male factory workers